Planktonic primary production and microbial respiration measured by C-14 assimilation and dissolved oxygen changes in coastal waters of the Antarctic Peninsula during austral summer: Implications for carbon flux studies - Aristegui, J.; Montero del Pino, María F.; Ballesteros Rodríguez, Salomé; Basterretxea Oyarzabal, Gotzon; Lenning, Kornelis van (Marine Ecology Progress Series, 2018)
Oxygen consumption and production and carbon fixation by micro-organisms were measured simultaneously in coastal surface waters near the Antarctic Peninsula. Although there was a good qualitative agreement between the oxygen and carbon measurements, total daily water-column integrated carbon incorporation measured by radiocarbon uptake in the particulate fraction underestimated net community production measured by the oxygen method by 29 to 54% (using a photosynthetic quotient of 1.5). Unaccounted-for exudation of dissolved organic carbon during the 14C uptake experiments may explain this discrepancy. Respiratory carbon losses by micro-organisms (largely phytoplankton) ranged between 10 and 50% of gross production, the highest values corresponding to the more productive stations. These estimates are, however, slightly conservative, since they refer to the upper 30 m of the water column, corresponding approximately to the euphotic zone in this region. Our results show that microbial respiration is an important part of the carbon flux of coastal Antarctic plankton. Unless it is considered in carbon flux models, the contribution of higher trophic levels to the carbon fluxes in marine food webs may be seriously overestimated. 201 191 SCIE